PENGARUH LIKUIDITAS, PROFITABILITAS, STRUKTUR MODAL DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN (Studi Kasus pada Perusahaan Sektor Properties dan Real Estate yang Terdaftar di Bursa Efek Indonesia Periode 2016 – 2021) - Monangin, Filia Gabrilia; Rosdiana, Riska (Universitas Mercu Buana, 2023)
This study examines and analyses the effect of Liquidity, Profitability, Capital Structure and Firmy Size on Firm Value in the Properties and Real Estate sectors listed on the Indonesia Stock Exchange. The research data is annual data for the 2016 – 2021 observation period obtained from the company's annual report. The sampling method used is purposive sampling; 10 companies met the sample criteria. The analytical method used in this study is panel data regression using the Fixed Effects model with an R2 value of 85.62%. The results showed that liquidity, profitability, and capital structure did not affect firm value, while firm size has a negative effect on firm value.